A phonetic grammar of the Polish language - Dyczkowski, Krzysztof; Nowakowski, Paweł; Kordek, Norbert; Stroński, Krzysztof (Investigationes Linguisticae, 2008)
The aim of the present paper is to give an overview of the investigation of the phonic articulatory systems of Polish on the basis of the detailed articulatory descriptions existent in phonetic literature and with the use computational tools. First the theoretical foundations of the phonetic grammar are briefly introduced, then the main problem of the choice of an appropriate repertory of phones for Polish is also discussed. The last section is devoted to the presentation of the computional amalysis of the collected data. The created application enables us to collect a given phonetic inventory, taking into consideration the division into particular languages and the database generated here makes further computer analyses possible. Owing to the introduction of numeric interpretation of the articulatory features and dimensions, the phones can be treated as vectors in n-dimensional metric space. Then the measures of distances can be employed as measures of similarity between respective phones. By means of applying the Data Mining algorithms the interdependencies in the set of phones can be automatically shown. The present paper is a first attempt to apply the axiomatic theory of language at the phonetic level to the analysis and synthesis of the phonetic system of Polish.